Effect of coiling temperature on the structure and properties of thermo-mechanically rolled S700MC steel - Oktay, Serkan; Di Nunzio, Paolo Emilio; Cesile, Maria Cristina; Davut, Kemal; Şeşen, Mustafa Kelami (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
Boron-free S700MC steel is usually produced exploiting the properties of a ferrite-bainite mixed microstructure formed by coiling the strips at a temperature of about 450°C, namely below the bainite start temperature. Aiming at further enhancing the mechanical properties for 6 to 10 mm thick strips, industrial trials with a coiling temperature of 600°C have been carried out to promote the formation of a structure of ferrite and carbides, which is also acceptable for this steel grade. Unexpectedly, a microstructure composed of ferrite and martensite has been obtained. Compared with the ferritic-bainitic grade, the new structure is characterized by a slight decrease of the yield point but by an increase of the ultimate tensile strength of not less than 80 MPa, with a transition from a quasi-discontinuous to a clearly continuous yielding behaviour. Accordingly, the yield-to-tensile strength ratio decreases from 0.90 to 0.75 and the impact energy decreases of 35 J and 60 J for the two gauge levels, respectively.The mechanical behaviour of the strips coiled at high temperature is explained as a direct consequence of the dual phase structure with hard phase interspersed in a soft ferrite matrix. The presence of martensite is justified by invoking the so-called incomplete bainite reaction. The partial transformation in ferrite after coiling and the long time necessary for the coil to cool down stabilize the not yet transformed austenite due to the carbon enrichment making the bainite formation impossible at lower temperatures.